In situ FTIR assessment of desiccation‒tolerant tissues. Issue 2 (2003) - Wolkers Wolkers, Willem F. Willem F.; Hoekstra Hoekstra, Folkert A. Folkert A.
Abstract : This essay shows how Fourier transform infrared (FTIR) microspectroscopy can be applied to study thermodynamic parameters and conformation of endogenous biomolecules in desiccation-tolerant biological tissues. Desiccation tolerance is the remarkable ability of some organisms to survive complete dehydration. Seed and pollen of higher plants are well known examples of desiccation-tolerant tissues. FTIR studies on the overall protein secondary structure indicate that during the acquisition of desiccation tolerance, plant embryos exhibit proportional increases in α -helical structures and that µ -sheet structures dominate upon drying of desiccation sensitive-embryos. During ageing of pollen and seeds, the overall protein secondary structure remains stable, whereas drastic changes in the thermotropic response of membranes occur, which coincide with a complete loss of viability. Properties of the cytoplasmic glassy matrix in desiccation-tolerant plant organs can be studied by monitoring the position of the OH-stretching vibration band of endogenous carbohydrates and proteins as a function of temperature. By applying these FTIR techniques to maturation-defective mutant seeds of Arabidopsis thaliana we were able to establish a correlation between macromolecular stability and desiccation tolerance. Taken together, in situ FTIR studies can give unique information on conformation and stability of endogenous biomolecules in desiccation‒tolerant tissues.